A Little On the Wild Side: Eaton's Prestige Fashion Advertising Published in the Montreal Gazette, 1952-1972 - Bosnitch, Katherine (Université Concordia, 2000)
Keywords: Eaton; Magasins; Montreal Gazette; Publicité

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Defrocking Dad: Masculinity and Dress in Montreal, 1700-1867 - Noel, Jan (Fashion. A Canadian Perspective, 2004)
Keywords: Papineau, Louis-Joseph; Ramezay, Claude de; Redpath, John; Vêtements

Montreal's Fashion Mile: St Catherine Street, 1890-1930 - Sifton, Elizabeth (Fashion. A Canadian Perspective, 2004)
Keywords: Rues; Sainte-Catherine (rue); Vêtements

Mainstreaming the Perception and Practice of Ethical Fashion in Montreal - Craven, Ryan John (Université Concordia, 2009)
Keywords: Vêtements

Fashion and Refuge: The Jane Harris Salon, Montreal, 1941-1961 - Ferrabee Sharman, Lydia (Fashion. A Canadian Perspective, 2004)
Keywords: Vêtements

Design and Innovation in Montreal through the 1960s and the 1970s - Sharman, Lydia Ferrabee (Material History Review / Revue d’histoire de la culture matérielle, 2005)
Keywords: Expositions; Place Ville-Marie; Transport en commun

Enduring Roots: Gibb and Co. and the Nineteenth-Century Tailoring Trade in Montreal - Cariou, Gail (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Le mouvement Slow Food à Montréal: reflet d'une nouvelle conscience alimentaire cosmopolite - Bélanger, Esther (Université Concordia, 2004)
Keywords: Alimentation

"Bonnie Lassies" and a "Coat of Many Colours": Highland-Inspired Clothing at the McCord Museum - Stack, Eileen (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Musée McCord; Musées; Vêtements; Écossais

Dicomode: dictionnaire de la mode au Québec de 1900 à nos jours - Baril, Gérald (Fides, 2004)
Keywords: Confection; Vêtements

L'Osstidcho ou le désordre libérateur - Roy, Bruno (Documents, 2008)
Keywords: Musique